Update on Current Hormonal and Non-Hormonal Contraceptive Options in Non-Human Primates - Remco A. Nederlof; Linda G. R. Bruins-van Sonsbeek; Job B. G. Stumpel; Jaco Bakker (Journal of Zoological and Botanical Gardens)
Reproductive success in captive non-human primates (NHPs) has increased the demand for safe, effective, and reversible population control methods. This review provides an overview of the current literature on hormonal and non-hormonal contraceptives as reproductive control methods in NHPs. Where available, behavioral and welfare implications, as well as drug efficacy, reversibility, and associated adverse effects, are considered. However, a paucity of data exists for NHPs, particularly in regard to non-hormonal contraceptives, emphasizing the need for institutions to share their experiences with reproductive management techniques in the species under their care.